Enhancing Connectedness Through Peer Training for Community-Dwelling Older People: A Person Centred Approach. (2nd June 2016) - Burmeister, Oliver K.; Bernoth, Maree; Dietsch, Elaine; Cleary, Michelle
Abstract : Social interaction and connectedness is important to the mental health and wellbeing of older people. The aim of this research study was to facilitate and increase opportunities for social connectedness for older people living in regional areas through the use of technology training. Weekly technology training sessions were conducted at a Seniors Citizen's Club with a peer trainer (an experienced, retired computer teacher) and sessions were attended not only by the six study participants, but also by other club members, with up to 15 club members participating in sessions. Data analysis involved all documents generated by the project, including the individual interviews, researcher observations of training sessions, reports from the peer trainer and weekly diaries maintained by participants. Findings demonstrated that computer training at the Senior Citizens Club helped participants build group cohesion and to form tiered connections with partners, family, and friends with whom they no longer live. When the trainer is seen as a peer, and training is person-centred, older people are more receptive to learning, exploring, and experimenting with technology. Although only six people were involved in the in-depth evaluation part of the study, voluntary training with the trainer in the absence of any funding continues even to this present time. The outcome of this research reinforces the potential for technology facilitated tiered connectivity to enhance the quality of life for older people living in regional and rural Australia.